Floristic survey of bryophytes in Bulosao watershed forest reserve, Lawaan, Eastern Samar - Casio, Aldrin Khynnard Yancy C. (2024)
The Bulosao Watershed Forest Reserve (BWFR), a lowland dipterocarp forest known for its four waterfalls, is situated in Lawaan, Eastern Samar. Bryophytes, which are moisture-dependent nonvascular plants thrive in this area and they hold significant ecological and medicinal value. This study determined the composition of bryophyte in the BWFR. Three 150-m transect lines were established in the location of the three of the four waterfalls. There were 56 species of bryophytes belonging to 30 genera and 17 families. There were 37 species of mosses belonging to 18 genera and 9 families, and 19 species of liverworts belonging to 12 genera and 8 families. The bryophytes found were epiphytic, epixylic, terricolous, saxicolous, and showed general preference on rocky substrate. Quadrats situated in riverbanks and in rivers were found to have a higher number of species and bryohyte cover. The bryophyte cover of BWFR amounted 10 1.3%. This relative low bryophyte cover is congruent to bryophyte covers in lowland forest and may be attributed to the microclimate, vegetation, and proximity to water bodies. The number of species revealed that it is the first study that documented the bryophytes species in the BWFR. Proper management of watersheds, floral surveys, and further studies are therefore deemed necessary for the preservation of this species.
Undergraduate thesis (B.S. Biology) --University of the Philippines, Tacloban.